Lexical Collocational Use by Thai EFL Learners in Writing - Siengsanoh , Boonyakorn (LEARN Journal: Language Education and Acquisition Research Network, 2021)
To achieve a high level of language fluency, learners need to possess sufficient collocational competence. However, collocation is considered a problematic area for many EFL learners, partly because of its arbitrariness. To gain more insight into the problems involving learners’ productive collocational skills, the current study examines lexical collocational use by Thai EFL learners in their writing. The writing of 90 university students were analyzed to show the proportion of six types of lexical collocations. Some observations regarding the differences in the use of lexical collocations by three groups of learners categorized according to language proficiency levels were made. The results suggested that verb-noun, adjective-noun, and noun-verb collocations were most frequently produced by all the three groups of learners. Interestingly, the higher level of language proficiency, the higher number of lexical collocations produced. Regarding the differences in their collocational use, the results point to the likelihood that the high-proficiency group used a wider variety of lexical collocations when compared to the other two groups, and that low-proficiency group used more generic and unclear vocabulary and produced several mistakes in terms of word choice. Based on the study results, some suggestions regarding how collocations could be taught more efficiently are presented.